Proceedings of the 17th ACM SIGPLAN Conference on Object-Oriented Programming, Systems, Languages, and Applications - OOPSLA ' 2002
DOI: 10.1145/582419.582437
|View full text |Cite
|
Sign up to set email alerts
|

Implementing distribution and persistence aspects with aspectJ

Abstract: This paper reports our experience using AspectJ, a generalpurpose aspect-oriented extension to Java, to implement distribution and persistence aspects in a web-based information system. This system was originally implemented in Java and restructured with AspectJ. Our main contribution is to show that AspectJ is useful for implementing several persistence and distribution concerns in the application considered, and other similar applications. We have also identified a few drawbacks in the language and suggest s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
170
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(176 citation statements)
references
References 12 publications
(10 reference statements)
0
170
0
6
Order By: Relevance
“…AOP emergenced as a new paradigm to modularize the concerns whose implementations would otherwise have been spread throughout the whole application, because of the limited abstractions of the underlying programming languages. Since then, several studies [15,16,17,19,35,36] have suggested that AOP is successful in modularizing crosscutting concerns. Unfortunately, these studies either wrongly identify modularization with the lexical SoC offered by AOP, or wrongly measure coupling in AO systems.…”
Section: Motivations and Goalsmentioning
confidence: 99%
See 2 more Smart Citations
“…AOP emergenced as a new paradigm to modularize the concerns whose implementations would otherwise have been spread throughout the whole application, because of the limited abstractions of the underlying programming languages. Since then, several studies [15,16,17,19,35,36] have suggested that AOP is successful in modularizing crosscutting concerns. Unfortunately, these studies either wrongly identify modularization with the lexical SoC offered by AOP, or wrongly measure coupling in AO systems.…”
Section: Motivations and Goalsmentioning
confidence: 99%
“…• EImp, which is an Eclipse Plugin that supports collaborative software development for distributed teams; • Health Watcher, which is a web-based information system that was developed by Soares [36] for the healthcare bureau of the city of Recife, Brazil. The system aims to improve the quality of services provided by the healthcare institution, allowing citizens to register complaints regarding health issues, and the healthcare institution to investigate and take the required actions.…”
Section: Selected Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soares et al [20] have reported their experience using AspectJ to implement distribution and persistence aspects in a web-based information system. They have implemented the system in Java and restructured it with AspectJ.…”
Section: Related Workmentioning
confidence: 99%
“…In all these cases however, AOP systems do not support the remote definition or application of aspects. Rather, non-distributed aspects are used to manipulate distributed infrastructures [49].…”
Section: Introductionmentioning
confidence: 99%